Managing human resources in nursing: the relationship of nurses’ working time and patients’ independence level - Čiarnienė, Ramunė; Suprikienė, Roberta; Čiutienė, Rūta; Daunorienė, Asta; Riklikienė, Olga (Journal of Business Economics and Management, 2019)
A skilled, competent, and motivated nursing workforce is crucial for a well-functioning health care system. Nurses’ professional activities done on a regular basis, their workload, and occupancy are related to the patient’s health status, dependence level and care needs. Therefore, managing human resources in nursing by effectively distributing nurses’ working time and monitoring their workload for safe and high quality care, managers should rely on the severity of patients’ health status and their independence level.In this article the results on how nurses’ working time depends on patients’ independence are provided. The research was carried out at a regional hospital, in departments of medical profile. The time-and-motion study was implemented with 72 observations made in total, which amounted to 777.2 hours of nursing time. A questionnaire was used to assess the level of patients’ independence by assessing the four activities of the patient’s daily living. The results revealed that the largest amount of nurses’ working time, i.e. almost half of a day’s shift, was spent on direct patient care by administrating medication use and performing various nursing procedures. Nurses would spend almost half of the time for direct patient care on completely dependent patients, while one third would be spent on dependent patients. The relative number of nurses’ contacts with a patient is directly proportional to patient’s level of independence; a strong or fairly strong linear relationship was established betweenn the level of patients’ independence and the relative amount of nurses’ working time.